Invitation to Syriac Christianity: an anthology - Penn, Michael Philip; Johnson, Scott Fitzgerald; Shepardson, Christine; Stang, Charles M. (University of California Press, 2022)
Despite their centrality to the history of Christianity in the East, Syriac Christians have generally been excluded from modern accounts of the faith. Originating from Mesopotamia, Syriac Christians quickly spread across Eurasia, from Turkey to China, developing a distinctive and influential form of Christianity that connected empires. These early Christians wrote in the language of Syriac, the lingua franca of the late ancient Middle East, and a dialect of Aramaic, the language of Jesus. Collecting key foundational Syriac texts from the second to the fourteenth centuries, this anthology provides unique access to one of the most intriguing, but least known, branches of the Christian tradition